(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This study is aimed to identify the relationship between the Information and Communication Technology (ICT) use in teaching and learning towards the achievement of school students. The purpose of this study was to investigate the effects of information and communication technology (ICT) on school from students’ perspectives.The purpose of this paper aims to bring together the findings and key points from a review of significant part of the available literature associated with ICTs for Education and ICTs in Education. This review set out to identify and evaluate relevant strategies in national and international research and initiatives related to measuring and demonstrating the effective use of ICT for education with regard to the teaching learning process; ICT and quality and accessibility of education; ICT and learning motivation, ICT and learning environment, and ICT to enhance the scholastic performance.Information and communication technologies (ICT) have become commonplace entities in all aspects of life. Across the past twenty years the use of ICT has fundamentally changed the practices and procedures of nearly all forms of endeavour within business and governance. Education is a very socially oriented activity and quality education has traditionally been associated with strong teachers having high degrees of personal contact with learners. The use of ICT in education lends itself to more student-centred learning settings. But with the world moving rapidly into digital media and information, the role of ICT in education is becoming more and more important and this importance will continue to grow and develop in the 21st century. In this paper, a literature review regarding the use of ICTs in education was provided. Effective use of ICT for Education along with ICT use in the teaching learning process; quality and accessibility of education; learning motivation Learning environment. Besides, an overview of the ICT and scholastic performance.